Evaluating climate shifts and drought regions in the central Indian river basins - Shekhar Singh; Vijay Jain; Manish Kumar Goyal (Scientific Reports)
Abstract Climate change, characterized by erratic rainfall patterns and rising temperatures, is enhancing the severity and intensity of drought across India. Considering this impact, assessment of these changes is critical for developing effective adaptation and mitigation strategies. This study employs a stochastic entropy-based approach to compute the inter- and intra-annual rainfall variability for multiple temporal scales. Considering this assessment, we identified winter, pre-monsoon, and post-monsoon seasons as key contributors to annual rainfall variability. Furthermore, using the entropy approach, we prepared a water resource availability map. It presents that 53.88% of the Betwa’s water resources and 54.57% of the Kshipra’s resources fall under Classes B and C, highlighting significant vulnerability to drought conditions in both basins. Subsequently, meteorological and hydrological droughts were evaluated using SPI, SPEI, and SRI indices. It showed that the Southern and Central regions of the Kshipra and the Northern and Central regions of the Betwa are highly drought prone. The outcome of the present study provides vulnerable drought regions with prolonged duration and high severity and intensity regions across the basin. It will support policymakers in implementing timely and targeted interventions for water resource management, facilitating the development of effective drought action plans.